Factors influencing purchase intention of smartphone: A case of Gen Z Malaysian consumers - Tan, W. H.; Kamarudin, D. (Inderscience, 2022)
New smartphone models and brands are bombarding the market at an alarming rate confusing consumers when it comes to their purchase intention. Consumer purchase intention is heavily influenced by a variety of factors from trends, to applications. This study aims to examine the factors influencing smartphone purchase intention among Gen Z consumers in Malaysia. Quantitative approach, purposive sampling method was employed to access the populations of Gen Z in Malaysia. Data was collected from 164 respondents through a structurally designed questionnaire. The proposed theoretical model was tested using PLS-SEM technique. The findings revealed that convenience was the main contributor to their smartphone purchase intention. This study contributes to the limited literatures in Malaysia, providing insights to the marketers, manufacturers, and academicians on what Gen Z Malaysian consumers think, as to what influences them the most when it comes to purchasing a smartphone.